Jesus and Afro-Pentecostal Prophets: Dynamics within the liminal space in Galilee and in Zimbabwe - Dube, Zorodzai (Hervormde teologiese studies, 2015)
What happens when religious and spiritual interventions are used to explain concrete social economic reality? This study suggests that Afro-Pentecostal prophets in Zimbabwe exist within the liminal context; the prophets therefore function to redefine and contest identities in view of present social realities. This realisation allows for a comparison between the Zimbabwean prophets and Jesus of Nazareth, with a view to draw general conclusions regarding the function of prophets. As contribution, the study fills the void within the studies concerning the religious explanations of socioeconomic issues in view of structures of power. Borrowing from Herbert Marcuse, this study advances the thesis that the prophets attract people by miracles and promises of bliss and, in the process, divert people’s attention from directly confronting structures of power and hegemony.